Liberalizing Capital Movements : Some Analytical Issues - Milesi-Ferretti, Gian (Economic Issues; Economic Issues ;, 2005)
This paper addresses the potential gains and risks of open capital markets by first looking at what classical economic theory suggests aboutthe benefits of capital mobility and then examining the counterargumentsarising from problems of incomplete information and other distortions.It shows that the risks of removing controls on flows of capital acrossnational borders are similar to those associated with removing controlson domestic financial institutions. The paper then explores how to manageliberalization to minimize the risks and maximize the benefits.